2022
DOI: 10.3390/educsci12030182
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Knowledge and Attitudes toward Digital-Game-Based Language Learning

Abstract: There is a good body of literature about digital-game-based language learning (DGBL), but research has mainly focused on students as game players rather than as future educators. This paper reports on a research conducted among 154 teacher candidates at a higher-education institution in Spain regarding the adoption of digital games in education. It analyzes the participants’ knowledge of and attitudes toward digital games in foreign language learning. Quantitative and qualitative data were gathered through a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Very often it was mentioned in this context that the game must serve a purpose for the school, and at the same time, the effort for introducing the game in class should be kept very low. These technical and pedagogical efforts were also reported in the findings of Belda-Medina and Calvo-Ferrer (2022).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Very often it was mentioned in this context that the game must serve a purpose for the school, and at the same time, the effort for introducing the game in class should be kept very low. These technical and pedagogical efforts were also reported in the findings of Belda-Medina and Calvo-Ferrer (2022).…”
Section: Discussionmentioning
confidence: 56%
“…This could be partially adapted for our study. Belda-Medina and Calvo-Ferrer (2022) were also able to show that a huge number of games are generally used by teachers regardless of aptitude. According to the teachers, the low effort and thematic components are particularly important for using games in the classroom.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As part of global development, schools in developing nations should encourage the use of computers by instructors to cultivate positive attitudes about ICT [ 34 , 35 ]. In addition, attitudes have a crucial influence on ICT integration, as the coefficient value of attitudes is greater than that of the other three components [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was true for both male and female instructors [ 35 ]. Meanwhile, in comparison to their more seasoned colleagues, beginner teachers had a more optimistic view of the use of ICT in instruction [ 36 ]. However, a few studies have found that there is no difference in instructors’ ICT use and views based on gender, age, or experience level [ 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%